Antecedents of Zakat payers trust in an emerging Zakat sector :an exploratory study - M.O.A., Mustafa; Mohamad, Muslim Har Sani; Adnan, Muhammad Akhyar (2011)
The main objective behind the establishment of effective governance in organisations is to ensure mutual trust among the stakeholders. Incidentally, virtually all studies on organisational trust have not investigated the role of governance in trust building. The aim of this paper is to report the mediating role of trust in the selection of zakat institutions by Nigerian zakat payers. Such knowledge will help zakat managers to influence zakat payers’ trust and patronage. The study explores antecedents of trust; and develops measurement scales which are used to explore the relationship between trust and the factors. Four factors: board capital, disclosure practices, nature of zakat institutions, and stakeholder management, were identified through the use of structural equation modeling as being the antecedents of trust. The implications for zakat institutions in building trust of zakat payers are also discussed. The zakat payer’s trust model represents the main contribution of this study.